Hubungan Pengetahuan Tentang Penggunaan Alat Pelindung Diri Dengan Penggunaan Alat Pelindung Diri Pada Petugas Pengangkut Sampah - Rizki Akbar (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Occupational Health and Safety (OHS) is one of the step that condacted to create a safe and healthy work environment. International labor organizations declare that in 2019 there were 2,78 million people who died due to work accidents, 1,95 million were caused by accidents that occurred in the work environment. Amount of work accidents in waste transporters contributes to the number of accidents in various regions as much as 81,000 cases per year. The use of PPE is one of the efforts to prevent work accidents. Using of PPE for waste transport workers that is hats, masks, clothes, gloves, boots. The aim of this research was to determine an overview of the use of PPE, knowledge of the use of PPE to the relationship between knowledge and the use of PPE in the Department of Environment and Forestry, in Bireuen Regency. Design of this study used an observational quantitative method with a cross-sectional research design. Sample in this study amounted to 64 respondents with was conducted a total sampling technique method. statistical test used is chi-square. research show that the completely use of PPE was 45,3%, incompletely was 54,7%. Knowledge of the use of PPE is good 56.3%, 43.8% inadequency. Conclusion of this research Based on the results of statistical tests obtained p value of 0.001 <0.05, this indicates that there is a significant relationship between knowledge and the use of PPE in the Waste Transporter of the Environment and Forestry Office of Bireuen Regency.